Canine leishmaniosis in Tunisia: Growing prevalence, larger zones of infection - Ali Bouattour; Amine Amri; Jaber Amine Belkhiria; Adel Rhim; Ons Fezaa; Jean-Charles Gantier; Youmna M'ghirbi (Public Library of Science (PLoS), 2021)
Background Discovered by Nicolle and Comte in 1908 in Tunisia, Leishmania infantum is an intracellular protozoan responsible for zoonotic canine leishmaniosis (CanL) and zoonotic human visceral leishmaniasis (HVL). It is endemic in several regions of the world, including Tunisia, with dogs considered as the main domestic reservoir. The geographic expansion of canine leishmaniosis (CanL) has been linked to global environmental changes that have affected the density and the distribution of its sand fly vectors. Methodology/Principal findings In this study, a cross-sectional epidemiological survey on CanL was carried out in 8 localities in 8 bioclimatic areas of Tunisia. Blood samples were taken from 317 dogs after clinical examination. Collected sera were tested by indirect fluorescent antibody test (IFAT; 1:80) for the presence of anti-Leishmania infantum antibodies. The overall seroprevalence was 58.3% (185/317). Among positive dogs, only 16.7% showed clinical signs suggestive of leishmaniosis. Seroprevalence rates varied from 6.8% to 84.6% and from 28% to 66% by bioclimatic zone and age group, respectively. Serological positivity was not statistically associated with gender. The presence of Leishmania DNA in blood, using PCR, revealed 21.2% (64/302) prevalence in dogs, which varied by bioclimatic zone (7.3% to 31%) and age group (7% to 25%). The entomological survey carried out in the studied localities showed 16 species of the two genera (Phlebotomus and Sergentomyia). P. perniciosus, P. papatasi, and P. perfiliewi were the most dominant species with relative abundances of 34.7%, 25% and 20.4%, respectively. Conclusions/Significance The present report suggests a significant increase of CanL in all bioclimatic areas in Tunisia and confirms the ongoing spread of the infection of dogs to the country's arid zone. Such an expansion of infection in dog population could be attributed to ecological, agronomic, social and climatic factors that affect the presence and density of the phlebotomine vectors. Author summary Visceral leishmaniasis caused by Leishmania infantum is an endemic disease in several regions of the world, especially, in the Mediterranean basin, where dogs constitute the main domestic reservoir for humans. This zoonotic vector-borne disease is closely associated with the environment. We carried out studies in 8 different regions of Tunisia, collecting and testing blood samples from 317 dogs. Out of which, more than half (58.3%) tested positive for L. infantum (IFAT+), although, only one-third of these displayed clinical signs. However, the detection of Leishmania DNA by blood PCR revealed a global prevalence in dogs of 21.2% (64/302) with a variation between bioclimatic zones. Our entomological survey revealed 16 sand fly species, dominated by the Phlebotomus and Sergentomyia genera, of which the most dominant were P. perniciosus, P. perfiliewi and P. papatasi. The first two of these are recognized vectors of L. infantum. Canine leishmaniosis continues to spread across Tunisia, moving southward, to arid zones because of global warming and agronomic and social factors affecting the presence and density of the phlebotomine vectors.